Road safety education as an effective intervention in school: a systematic literature review - Shahril, Roziana; Sidek, Suriati (Asian Scholars Network, 2023)
Evidence shows that Road Safety Education (RSE) can instil new knowledge and promote positive road safety behaviours. This systematic literature review examine documents on RSE implementation as and intervention to improve behaviour, give new information and to change negative perception on the importance of road safety among school children. The researcher follows PRISMA guidelines for the review and search has been conducted in SCOPUS to find relevant documents. 194 records have been identified and after the screening, only 20 eligible documents were retrieved for further evaluation. Quality appraisals were conducted using Quality Assessment with Diverse Studies (QuADS). 11 documents were included in the systematic review. The review has shown that many types of approaches can be used in order to conduct RSE. However, it has to suits the sample in focus because each sample has different characteristics and unique needs. The systematic review also proven that any type of programs can exert a significant difference before and after intervention. However, the effect size is not the same and would be differ according to the population in the target. Hence, RSE remain as an important tool to cultivate positive road safety behaviour, knowledge and perception. Further research should rigorously studies RSE scientifically in order to ensure the effectiveness is measured correctly and to guide the implementation of RSE in different setting.